The Values of Tolerance in the Hadith of the Prophet: A Study of Its Application in Banyuwangi Regency - Nasirudin Al Ahsani (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2023)
In Article 29, Paragraph 2 of the 1945 Constitution, it is stated that the State guarantees the freedom of every citizen to embrace their own religion and worship according to their religion and beliefs. However, in recent years, religious discrimination has persisted. In 2022, a man vandalized the Dipa Giri Sakti Temple in Kediri, while in 2019, a controversy arose regarding the construction of a temple in Bekasi. In the same year, the Padmosari statue, a Hindu religious symbol in Argosari Village, was damaged, allegedly by irresponsible individuals. Research Objectives: 1) To analyze the values of tolerance in the Prophet's hadith, and 2) To analyze the application of tolerance from the Prophet's hadith in Banyuwangi. This study uses a qualitative research method, with data collection techniques including interviews, observations, and documentation. Findings: 1) Tolerance in the teachings of Prophet Muhammad SAW emphasizes mutual respect and appreciation for differences, both among Muslims and with followers of other religions. The hadiths stress the importance of moderation, dialogue, and compassion in resolving differences. Ahmad Syarif Yahya in Ngaji Toleransi and Fikih Toleransi also asserts that Islam encourages tolerance without diminishing individual beliefs. The Prophet, through sirah nabawiyyah, shows that religious moderation and tolerance are key to harmonious social interactions. 2) In Bangorejo and Sambimulyo Districts, Muslims and non-Muslims cooperate to ensure the smooth running of religious celebrations, such as Eid al-Fitr and Galungan. The hadith